Rectus Fascia Versus Fascia Lata for Autologous Fascial Pubovaginal Sling: A Single-Center Comparison of Perioperative and Functional Outcomes. Issue 8 (August 2020) - Peng, Michelle; Sussman, Rachael D.; Escobar, Christina; Palmerola, Ricardo; Pape, Dominique M.; Smilen, Scott S.; Rosenblum, Nirit; Brucker, Benjamin M.; Peyronnet, Benoit; Nitti, Victor W.
Abstract : Objective: To compare perioperative and functional outcomes of autologous fascia lata versus rectus fascia pubovaginal sling in female patients with stress urinary incontinence (SUI). Methods: The charts of all patients undergoing pubovaginal sling for SUI from 2012 to 2017 at a single center were retrospectively reviewed. Patients were divided into 2 groups: those with the sling harvested from the fascia lata (FL group) and those with the sling harvested from the rectus fascia (RF group). Results: Between 2012 and 2017, 105 women underwent pubovaginal slings: 21 using FL and 84 using RF. Operative time did not differ significantly between the FL and RF groups (84 vs 81.9 minutes; P =0.68). Estimated blood loss was lower in the FL group (91.7 vs 141.6 mL; P =0.04). There were more wound complications in the RF group, although this was not statistically significant (0% vs 14.3%; P =0.12). Overall complications were comparable between FL and RF groups (52.4% vs 48.9%; P =0.81), but the proportion of Clavien grade 2 or greater were higher in the RF group (4.8% vs 20.2%; P =0.11). Overall, wound complications accounted for 29.3% of postoperative complications in the RF group (12/41). Functional outcomes were comparable between FL and RF groups, with similar rates of patients without SUI symptoms after 1 month (82.4% vs 76.4%; P =0.74), 1 year (55.6% vs 63.8%; P =0.76), and at the latest follow-up (66.7% vs 65.8%; P =0.87). Conclusions: When compared with rectus fascia for pubovaginal sling, fascia lata may decrease perioperative morbidity, especially wound complications, without compromising functional outcomes.